2009
DOI: 10.1007/s10815-009-9368-9
|View full text |Cite
|
Sign up to set email alerts
|

Does first polar body morphology predict oocyte performance during ICSI treatment?

Abstract: Purpose To gain insight into the morphology of the first polar body (1 PB) in ICSI patients and to explore whether it could predict mature oocyte viability and performance in this setting. Methods Seventy two consecutive women planned to perform ICSI treatment were prospectively recruited for this study. All oocytes retrieved underwent evaluation for nuclear maturity and accurate assessment of 1 PB morphology. MII oocytes were cultured in separate groups in each woman in accordance with two different categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…Previous studies have demonstrated that PB1 morphology is related to mature oocyte viability, and have the potential to predict oocyte performance and pregnancy achievement in infertile women undergoing intracytoplasmic sperm injection (ICSI) treatment (Younis et al , 2009). Recently, it has also been found that PB1 morphology may reflect the development competence of oocytes in vitro (Rose & Laky, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that PB1 morphology is related to mature oocyte viability, and have the potential to predict oocyte performance and pregnancy achievement in infertile women undergoing intracytoplasmic sperm injection (ICSI) treatment (Younis et al , 2009). Recently, it has also been found that PB1 morphology may reflect the development competence of oocytes in vitro (Rose & Laky, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes with intact or smooth PB1 can generate better second-day embryos, greater blastocyst yields, and increased pregnancy and implantation rates (Younis et al , 2009; Rose & Laky, 2013). It has also been found that embryos in the intact or smooth PB1 group show increased rate of blastocyst formation compared with the fragmented PB1 group ( P < 0.05) (Navarro et al , 2009; Rose & Laky, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During maturation and fertilization, the human oocyte releases the first and second polar body (PB 1 and PB 2 ), respectively, via two asymmetric divisions (meiosis). The relationship between PBs and oocytes has attracted much attention because of the homology of their chromatin with the oocytes (Munné et al, 1995;Ebner et al, 1999Ebner et al, , 2000Ebner et al, , 2002Durban et al, 2001;Verlinsky 2003;Fancsovits et al, 2006;Younis et al, 2009;Halvaei et al, 2011;Reich et al, 2011). However, most research has focused on PB 1 and controversy still exists (Munné et al, 1995;Ebner et al, 1999Ebner et al, , 2000Ebner et al, , 2002Durban et al, 2001;Verlinsky 2003;Fancsovits et al, 2006;Younis et al, 2009;Halvaei et al, 2011;Reich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies involving intrauterine transfer of small numbers of in vivo-derived horse embryos were not very successful (Allen & Rowson 1975, Ball et al 1989, Weber et al 1993, but 'premature intrauterine transfer' with large numbers of day 2-3 IVP horse embryos has not been described previously. In this latter respect, while it is common practice to culture embryos to the blastocyst stage before intrauterine transfer in most domestic species, in human medicine, premature intrauterine transfer of day 2 and 3 IVP embryos is a routine procedure that yields good results (Younis et al 2009) and circumvents the potential downsides of prolonged in vitro culture or the difficulty of transferring early embryos to the oviduct. Currently, blastocyst rates of 25-35% can be obtained after ICSI and in vitro culture of cleaved horse embryos (Hinrichs 2010).…”
Section: Introductionmentioning
confidence: 99%